Analisis Faktor-Faktor yang Memengaruhi Stunting di Provinsi Nusa Tenggara Timur Tahun 2019-2023 - Tristy Welas Ulas Jati; Muhamad Sukin; Ashtian Ultanti (Jurnal Statistika Terapan (ISSN 2807-6214), 2024)
Stunting is a nutritional problem that often occurs in toddlers which is characterized by height growth that is shorter than the age standard. Based on Survei Kesehatan Gizi Indonesia 2023, NTT's stunting prevalence is at 37.9 percent, which is the second highest province in Indonesia. The aim of this research is to see what indirect factors influence the incidence of stunting in NTT province. These factors are exclusive breastfeeding, Low Birth Weight (BBLR), average length of schooling (RLS), households with access to adequate sanitation, households with access to adequate drinking water, and expenses for households with toddlers. The research results of multiple linear regression analysis at a significance level of 5% with a value of 0.002 for the variable access to adequate sanitation and 0.05 for the variable expenditure for households with toddlers. The conclusion is that there is a relationship between adequate sanitation and household expenditure on the prevalence of stunting in NTT province.